2020
DOI: 10.1016/j.brs.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial electrical stimulation motor threshold can estimate individualized tDCS dosage from reverse-calculation electric-field modeling

Abstract: Background: Unique amongst brain stimulation tools, transcranial direct current stimulation (tDCS) currently lacks an easy or widely implemented method for individualizing dosage. Objective: We developed a method of reverse-calculating electric-field (E-field) models based on Magnetic Resonance Imaging (MRI) scans that can estimate individualized tDCS dose. We also evaluated an MRI-free method of individualizing tDCS dose by measuring transcranial magnetic stimulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 74 publications
3
66
0
Order By: Relevance
“…Despite the effectiveness of tDCS, one major limitation is inter-individual differences in response [12][13][14]. The intensity and distribution current flow through the brain, reflected in the electric field (EF) magnitude across the brain, is one main reason hypothesized for the individual variations [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effectiveness of tDCS, one major limitation is inter-individual differences in response [12][13][14]. The intensity and distribution current flow through the brain, reflected in the electric field (EF) magnitude across the brain, is one main reason hypothesized for the individual variations [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Having said that, we would like to highlight that the work of Evans et al, [28] and Caulfield et al, [33] have added another parameter that the user can calculate with भ -SATA i.e., the individualized dosage of current. We will explain this with an example for an ) .…”
Section: Discussionmentioning
confidence: 99%
“…Even though traditionally tDCS has less spatial resolution compared with other brain stimulation techniques (i.e., transcranial magnetic stimulation, TMS), increasing research literature shows that tDCS stimulation over M1 can successfully interfere with the area's involvement in action perception and execution (Nitsche & Paulus, 2000). Nevertheless, some recent studies have indicated that response to tDCS stimulation can be quite variable between participants (Nitsche & Paulus, 2001;Tremblay, Beaulé, Lepage, & Théoret, 2013), with some of them reporting that only 60% of subjects are experiencing the classic tDCS interference effect, thus supporting the need for a method of individualizing tDCS dosage which uses electric-field (E-field) modelling (Bikson, Rahman, & Datta, 2012;Datta, Truong, Minhas, Parra, & Bikson, 2012;Evans et al, 2020), to allow for more consistent responses to tDCS stimulation (Caulfield et al, 2020). We acknowledge that in the present study we did not test our participants for a canonical response to M1 tDCS before enrolling them.…”
Section: Discussionmentioning
confidence: 99%